The effect of tumor volume on radiotherapy outcome and correlation with other prognostic factors in patients with T2 supraglottic cancer - Rutkowski, Tomasz W.; Maciejewski, Bogusław; Kołosza, Zofia; Wygoda, Andrzej; Składowski, Krzysztof; Hejduk, Beata; Rutkowski, Roman (Contemporary Oncology/Współczesna Onkologia, 2014)
The retrospective chart review of 110 patients with T2 supraglottic cancer who underwent radiotherapy was performed to correlate tumor volume with other prognostic factors and to analyze its impact on treatment results. Patients with involved nodes, poor histopathological tumor differentiation, or hemoglobin concentration ≤ 14.3 g/dl had significantly larger tumors. Patients with large tumors had significantly lower 5-year local control rate, overall survival rate and presented significantly higher risk of nodal involvement and the ratio of poor histopathological differentiation of the tumor. Tumor volume significantly impacts radiotherapy outcome and should be considered to optimize treatment strategy for patients with T2 supraglottic cancer.